Elitism: normative ethics of local organisation in community-based natural resources management. Issue 5 (7th November 2016) - Yadav, Bhagwan Dutta; Bigsby, Hugh R.; MacDonald, Ian
Abstract : Purpose: Local organisations have been established on participatory approach whose central purpose is to establish development activities bringing about positive change as four pillars of developments: to establish decentralised robust local organisation for sustainable forest management to enhance livelihood of rural people, to meet the forest products basic needs of local people, targeted interventions for poverty alleviation and social mobilisation initiatives and biodiversity conservation climate change mitigation and adaptation. Design/methodology/approach: Local organisational elites designed/conceptualised the concept, where it can be operated organisationally and in local organisational context that provides new ways and methods to develop conceptual framework (Table I ), which sheds light on involvement of poor and underprivileged members in decision-making process and distribution of benefit on equity basis. Findings: The findings will lead to a positive change through the organisational elite model through both reorganising organisations and restructuring of power with change in the society and reduce the impact of rational choices, vested interests of elites (leaders of local organisation) and political factors, which are otherwise playing a game or tragedy of commons. Research limitations/implications: Because of the limited resources and time, the authors are unable to verify it on the other development line agencies such as drinking water scheme, livestock, health and cooperative. Practical implications: It considerably appears that the impacts are very sound to conclude from the review of above models of elites that provide a very clear understanding and useful conceiving lens to formulate how participation occurs in the executive committee of the community forestry user groups (CFUG) and community-based organisations based on three key elements. First are the caste and the caste structure of the community. Second is the wealth status of the individual, and third is power created both from wealth and caste. This should be determined from the local organisational elite model (Table I ) about the nature of interactions on the executive of the CFUGs and other vehicles of local community-based development organisations. Social implications: Local organisations will provide an opportunity in reality to both elites and non-elites to considerably change, make aware and create a realistic situation to determine the dialectical opportunity to develop relationship, interaction and configuration between elite and non-elite members both outside and inside of the local organisations. Originality/value: It has not been found in literatures yet such sort of concept developed in development field particularly in the development activities performed by participation of local users. Hence, it is certainly original conceptual framework.